2013
DOI: 10.1007/s00284-013-0338-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fecal Lactobacillus Community Structure in Patients with Early Rheumatoid Arthritis

Abstract: The objective of this study was to analyze human fecal Lactobacillus community and its relationship with rheumatoid arthritis. Samples taken from rheumatoid arthritis (RA) patients and healthy individuals were analyzed by quantitative real-time PCR. Bacterial DNA was extracted from feces, and amplicons of the Lactobacillus-specific regions of 16S rRNA were analyzed by denaturing gradient gel electrophoresis. The richness, Shannon-Wiener index, and evenness of gut microbiota of both groups were analyzed to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(141 citation statements)
references
References 28 publications
12
127
0
2
Order By: Relevance
“…The role of Collinsella in altering gut permeability and disease severity has been confirmed in experimental arthritis [16]. A more recent study evaluated human fecal Lactobacillus community and its relationship with RA [17]. Samples obtained from RA patients and healthy individuals were analyzed and demonstrated that fecal microbiota of RA patients contained significantly more PG produces a unique bacterial enzyme, P. gingivalis peptidyl-arginine deiminase (PPAD), which has the ability to convert arginine residues in proteins to citrulline.…”
Section: Gastrointestinal Microbiota In Rheumatoid Arthritis Patientsmentioning
confidence: 99%
“…The role of Collinsella in altering gut permeability and disease severity has been confirmed in experimental arthritis [16]. A more recent study evaluated human fecal Lactobacillus community and its relationship with RA [17]. Samples obtained from RA patients and healthy individuals were analyzed and demonstrated that fecal microbiota of RA patients contained significantly more PG produces a unique bacterial enzyme, P. gingivalis peptidyl-arginine deiminase (PPAD), which has the ability to convert arginine residues in proteins to citrulline.…”
Section: Gastrointestinal Microbiota In Rheumatoid Arthritis Patientsmentioning
confidence: 99%
“…Epidemiologic data indicate probable associations between mucosal immunity and the development of RA [109][110][111][112][113], and several mucosal sites have been suggested to be involved in the pathogenesis of RA.…”
Section: Mucosal Sitesmentioning
confidence: 99%
“…Liu et al (36) Gut microbiome DMARD-naive patients with early RA had increased Lactobacillus abundance and diversity compared to healthy controls. Zhang et al (39) Gut microbiome Dysbiosis in the gut (and oral) microbiome of patients with RA was partially resolved after RA treatment; Lactobacillus salivarius was overrepresented in patients with RA, while Haemophilus strains were relatively depleted.…”
Section: Gutmentioning
confidence: 99%
“…Altering the local T cell balance in this way may lead to systemic autoimmunity. Indeed, several studies have demonstrated that gut dysbiosis occurs in RA (36)(37)(38)(39) and that specific bacteria, including Lactobacillus (36) and Prevotella copri (37), are more abundant in new, untreated RA patients.…”
Section: Gutmentioning
confidence: 99%